Computer-assisted preoperative planning of reduction of and osteosynthesis of scapular fracture: A case report - Madeja Roman (De Gruyter, 2021)
Reports on the use of computer-assisted trauma surgery of comminuted scapula fracture are still quite rare. In this article, we present a case of comminuted scapula fracture, the surgical reconstruction of which was pre-operatively planned using a complex software solution.